The impact of migration on the development of chinese dialects - Ibrasheva, D. R. (Journal of Oriental Studies, 2016)
Chinese language is characterized by a variety of dialects, but so different, that people from different provinces can’t understand each other. Migration is the main reason of dialects appearing in China. The main part of the vocabulary of Chinese dialects inherited from the ancient Chinese language. However, as a result of communication with neighbor nationalities, Chinese dialect vocabulary has enriched. The main reasons for the large migrations have been political and natural disasters. Migration led to the isolation of large groups of Chinese people with subsequent development of specifi c dialects.